Incidence of concurrent systemic injuries with traumatic proptosis and its effect on outcome – 100 dogs - Whinery, Nicole; Allbaugh, Rachel A.; Sebbag, Lionel; Walton, Rebecca (Frontiers in Veterinary Science, 2024)
ABSTRACT Objective – To evaluate the incidence of concurrent systemic injuries in dogs and cats with traumatic ocular proptosis and their effect on survival to discharge. and visual outcome. Additionally, to evaluate for associations between the type of trauma, each presenting vital signs, minimum laboratory database findings including packed cell volume, total solids, plasma glucose and lactate concentrations, and the diagnosis of concurrent systemic injury and survival., survival, and visual outcome. Design – Retrospective study between the years 2017 - 2022. Setting – One university teaching hospital and one large, private practice. Animals – 1005 animals dogs presenting to the hospital with a diagnosis of traumatic ocular proptosis. Measurements and main results – Medical records were retrospectively reviewed; signalment, species, breed, sex, age, weight, date of presentation, type of trauma sustained, time from trauma to presentation, vitals on presentation, and minimum laboratory database findings including packed cell volume (PCV), total solids (TS), plasma glucose concentration and plasma lactate concentration were recorded. A modified animal trauma triage (ATT) score was retrospectively calculated. A total of 17 21 patients dogs (17%) had concurrent systemic injury. including 17/100 dogs (17%) and 4/5 cats (80%). Compared to patients dogs without systemic injuries, patients dogs with systemic injuries had a significantly lower body temperature (median 101.1 °F (38.3 °C) vs. 101.6 °F (38.6 °C), respectively; P = 0.008), significantly lower PCV values (median 40% vs. 46%; P = 0.04) and significantly higher plasma glucose concentrations (125 mg/dL, 6.9 mmol/L vs. 112 mg/dL, 6.2 mmol/L; P = 0.012) and approaching statistical significance, lower PCV values (median 40% vs. 46%; P = 0.051).. There was no difference in visual outcome in systemically injured vs. non-systemically injured animals (P = 0.218). Conclusions – Patients Dogs presenting with traumatic ocular proptosis do present with concurrent systemic, non-ocular injuries; however, these concurrent injuries do not seem to be associated with survival to discharge. or visual outcome.